The Alarm Fatigue Challenge in the Neonatal Intensive Care Unit: A “before” and “after” Study - Stiglich, Yanin Fontana; Dik, Pablo H. Brener; Segura, Maria S.; Mariani, Gonzalo L. (American Journal of Perinatology, 2023)
Objective Alarm fatigue (AF) happens when professionals are exposed to many alarms and they become desensitized to them. It is related to proliferation of devices, not standardized alarm limits, and high prevalence of “nonactionable alarms,” i.e., false alarms (triggered by equipment issues) or nuisance alarms (physiological change not requiring clinical action). When AF happens, response time seems to be longer and important alarms could be dismissed. After evaluating the situation in our neonatal intensive care unit (NICU), an alarm management program (AMP) was developed to reduce AF. The objective of this study were to compare the proportion of true alarms, nonactionable alarms, and to measure response time to alarms in the NICU before and after implementing an AMP and also to determine variables associated with nonactionable alarms and response time.Study Design This was a cross-sectional study. A total of 100 observations were collected between December 2019 and January 2020. After an AMP was implemented, 100 new observations were collected between June 2021 and August 2021. We estimated the true and nonactionable alarms proportion. Univariate analyses were performed to determine variables associated with nonactionable alarms and response time. Logistic regression was performed to assess independent variables.Results The proportion of true alarms before and after AMP was 31 versus 57% (p = 0.001), whereas the proportion of nonactionable alarms was 69 versus 43% (p = 0.001). Median response time was significantly reduced (35 versus 12 seconds; p = 0.001). Before AMP, neonates with less intensive care needs had a higher proportion of nonactionable alarms and a longer response time. After AMP, response time was similar for true and nonactionable alarms. For both periods, the need of respiratory support was significantly associated with true alarms (p = 0.001). In the adjusted analysis, response time (p = 0.001) and respiratory support (p = 0.003) remained associated with nonactionable alarms.Conclusion AF was highly prevalent in our NICU. This study shows that after the implementation of an AMP, response time to alarms and the proportion of nonactionable alarms can be significantly reduced.Key Points
Keywords: alarm fatigue; patient safety; clinical alarms; neonatal intensive care